Proteção de dados pessoais da criança: privacidade, vulnerabilidade e consentimento na sociedade da informação - Eberlin, Fernando Büscher von Teschenhausen (2019)
Obtaining prior consent for data collection in mass consumer relations is a controversial issue, especially when it involves people who cannot enter into a contract, such as children. Nevertheless, these young consumers use products and services that collect data, which generates legal effects. This scenario creates discussions about the possibility of parents to consent in the place of their children, which is not a unanimous solution given the very personal character of data processing as well as the possible harms to privacy. In addition, the use of data in marketing communication to children may be abusive and not aligned to their best interests. This thesis, using the hypothetical-deductive method, addresses the issue of children`s personal data protection when they use products and services connected to the internet. In Chapter One, information society`s issues (such as the concept of big data, the imposition of power arising from technology by companies and States and business models based on free goods and services) are analyzed. Then, Chapter Two reinterprets the concept of privacy, placing it in the context of information society and personal data protection. Chapter Three analyses the concept of childhood and the need to ensure children`s development and autonomy rights, as well as their hypervulnerability as consumers and the worsening of this condition in the digital environment. Finally, Chapter Four studies the mechanisms of consent in the cyberspace and the possible regulatory alternatives to the current parental consent model, commonly applied when it comes to children`s personal data protection.